(untitled) (CIPEEX, 2025)
Introduction: Vaccination is a right to health, and the Hepatitis B vaccine (recombinant) (VCHB) is the most effective vaccine for preventing this disease. However, there have been significant declines in most vaccines, accentuated by the Coronavirus pandemic and anti-vaccine movements. Objectives: To identify the prevalence of Hepatitis B vaccination coverage in children up to 2 years of age in the pre-pandemic and post-pandemic periods, as well as the impact of the pandemic and anti-vaccination movements on Hepatitis B vaccination coverage. Methodology: This is a retrospective quantitative study based on data on childhood vaccination coverage in the Midwest and the national scenario between 2018 and 2021 for Hepatitis B vaccines, obtained from the Department of Informatics of the Unified Health System (DataSUS). Results: Hepatitis B vaccination coverage in children under 30 days of age showed widespread declines both nationally and in the Midwest region, with the largest decline occurring during the pandemic period, particularly in Mato Grosso do Sul. Regarding the doses of Hepatitis B vaccines administered to individuals up to 2 years of age, there were decreases between 2018-2019 and 2020-2021 of approximately 13.11% and 12.02% in the Midwest. Conclusion: Reductions in hepatitis B vaccination coverage were observed in children up to 2 years of age, with the Midwest region presenting the lowest number of doses administered between 2018 and 2021, with a focus on Mato Grosso do Sul, demonstrating a direct or indirect relationship with the challenges analyzed.